LAW ENFORCEMENT OF ILLEGAL LOBSTER CLEAR SEED DISTRIBUTION CRIME - Wahyudi, Tri; Prawesthi, Wahyu; Khoidin, M. (YURIS: Journal of Court and Justice, 2023)
Indonesia is an archipelago that is rich in flora and fauna both on land and sea. It causes some people to commit criminal acts, especially criminal acts in distributing lobster clear seeds illegally and not fulfilling fisheries licenses in Indonesia. Therefore, serious efforts are needed to tackle these fisheries crimes. The objective of this research is to find out the effectiveness of law enforcement regarding illegal distribution of lobster clear seed; and to observe the law enforcement attempts against its case. The approach method used in this research is juridical normative approach. The juridical normative approach is an approach that uses legislation by examining all laws and regulations related to the legal issues being addressed and conceptual approaches derived from views and doctrines that develop in legal science. The regulation on the prohibition of marketing clear lobster seeds is regulated in the Minister of Marine Affairs and Fisheries Regulation No. 12/PERMEN-KP/2020 concerning the Management of Lobsters, Crabs and Rajungan in the Republic of Indonesia and amended to the Minister of Marine Affairs and Fisheries Regulation No. 17/2021 concerning the Management of Lobsters, Crabs and Rajungan in Indonesian territorial waters.